Devolution of health care services in the Philippines - Ferrer, Alice Joan G. (Iloilo City, Philippines University of the Philippines Visayas, 2002)
"In the Philippines, the Local Government Code of 1991 devolved to the local government units the responsibility to deliver various aspects of health care services. This was met with resistance by the local government units and the public health system, which were not ready to meet the challenges of health care service devolution. Despite the problems of implementation, finance, and structure, health care service devolution continues. The impact of devolution has been great and will undoubtedly shift and evolve. Vigilance is still important in the attempt, through devolution, to create a more efficient and equitable health care system."
Keywords: Department of Health; Health facilities -- Philippines; Health Care Services